Life history of the humpnose big‐eye bream Monotaxis grandoculis. Issue 6 (13th May 2022) - Pardee, Cassandra; Wiley, John
Abstract: This study provides estimates of growth rate, longevity, maturity, spawning seasonality and mortality for Hawai'i's only lethrinid, the humpnose big‐eye bream (known as Mū in Hawai'i) Monotaxis grandoculis, a commercially and recreationally important species in Hawai'i and throughout the Indo‐Pacific. M . grandoculis reaches maturity at 303 mm fork length or 3.6 years of age for both sexes. Males were significantly larger than females for a given age. The von Bertalanffy growth parameters for males and females were L ∞ = 506 mm fork length and von Bertalanffy growth coefficient ( K) = 0.24 year −1, and L ∞ = 427 mm fork length and K = 0.33 year −1, respectively. Both males and females reached ages over 20 years old, with a maximum age of 23 years. M . grandoculis had a distinct spawning season from May through August with corresponding elevated female gonadosomatic index. An age‐based multinomial catch curve indicated that the commercial exploitation rate (natural mortality/fishing mortality) was 0.48 year −1, which is considered below the overfishing limit.